5, 10‑Methylenetetrahydrofolate reductase (MTHFR) C677T/A1298C polymorphisms in patients with nonsyndromic cleft lip and palate. Issue 6 (21st September 2020) - KOMIYAMA, YUSKE; KOSHIJI, CHIKAKO; YOSHIDA, WAKA; NATSUME, NAGATO; KAWAMATA, HITOSHI
No abstract available